A higher global diet quality score is associated with lower risk of obesity among male university students in Lebanon: a pilot study - Najwa Mourad; Samer Kharroubi; Lara Nasreddine; Nahla Hwalla (Frontiers in Nutrition)
ObjectiveThis pilot study aims to assess the diet quality amongst Lebanese male university students using the Global Diet Quality Score (GDQS), identify its association with obesity, and determine the key drivers of consumption of foods associated with higher NCDs risk.MethodsA cross-sectional survey was conducted using a convenience sampling approach, comprising 385 male students aged between 18 and 24 years at the American University of Beirut. Dietary data was collected using 24-h recall, where participants detailed all foods and beverages consumed in the past 24 h, including portion sizes. Sociodemographic, anthropometric, lifestyle factors and drivers of food consumption data were also collected. GDQS scores were categorized as high (≥23), moderate (15–23), or low (< 15) indicating low, moderate and high NCD risk, respectively. A multiple logistic regression was applied to assess association of GDQS with sociodemographic and anthropometric variables.ResultsThe results showed that the majority of male university students had low (47%) or moderate (47%) GDQS scores, with only a small proportion (4%) showing high scores. Foods contributing to low GDQS scores were determined, with taste emerging as the primary factor influencing food group consumption. Additionally, individuals in health-related majors and higher academic year of study had higher GDQS scores, and those with higher GDQS scores had a lower risk of obesity. The study findings suggest that a high proportion of the study sample are at a higher risk of NCDs given their dietary quality, demonstrated an association between low GDQS scores and obesity risk, and identified education as a predictor of diet quality.ConclusionThis study calls for larger studies assessing dietary habits and quality amongst Lebanese university students to provide context-specific evidence for the development of targeted interventions aimed at the promotion of healthier eating habits in this population group and curbing the NCDs epidemic in the country.